Results from Estonia's 2022 Report Card on Physical Activity for Children and Youth: Research Gaps and Five Key Messages and Actions to Follow - Evelin Mäestu; Merike Kull; Jarek Mäestu; Maret Pihu; Kristjan Kais; Eva-Maria Riso; Andre Koka; Henri Tilga; Jaak Jürimäe (MDPI AG, 2023)
The aim of this article is to summarize the results of the 2022 Estonian Physical Activity Report Card across 10 indicators based on available scientific data and national databases, and, additionally, to compare the current results with previous Report Card results. A national expert panel, consisting of research and policy experts, identified the available sources and synthesized as well as graded relevant data related to the physical activity (PA) of Estonian children and youth. Grade B was assigned to Organized Sports and Physical Activity (B−), Community and Environment (B+), and Government (B). Grade C was assigned to Overall Physical Activity (C+), Physical Fitness (C+), Family and Peers (C−), and School (C+). The lowest grade, D, was assigned to Active Play (D), Active Transportation (D+), and Sedentary Behaviors (D−). In Estonia, the participation rate in organized sport is relatively high, and government in addition to community support seem to be at a relatively good level. However, a relatively high number of children and youth did not meet the current PA guidelines, and the levels of sedentary behavior and screen time were very high. The PA of children and youth should be a cross-disciplinary priority, and focus should be put on developing schoolyards and outdoor breaks, varied and easily accessible organized sport, the use of active transportation, and the implementation of physical education that supports leisure time activities.